The Effect of Leadership Style and Job Satisfaction on Employee Performance at Yogya Plaza Cimahi - Nursiti; Herman Sofyandi (Technium Social Sciences Journal, 2021)
Skilled human resources will produce satisfying work results. Therefore companies need to realize the importance of improving employee performance, as happened to Yogya Plaza Cimahi. Leaders have an important role to play in mobilizing subordinates to produce good performance. In addition, employees who are satisfied with what they get from the company will continue to strive to improve their performance. This study aims to examine and analyze the influence of leadership style and job satisfaction on employee performance in Yogya Plaza Cimahi. The low employee performance is thought to be caused by the lack of optimal leadership style and low job satisfaction. The research method uses descriptive and verification, the data source uses primary data through questionnaires. The research sample was 57 respondents. The results showed that descriptively the leadership style, job satisfaction, and employee performance were classified as lacking. As for verificatively, it shows that leadership style and job satisfaction have a significant effect on employee performance either partially or simultaneously